(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The pharmaceutical industry holds a huge market, the interests of which might clash with the corresponding benefit that both patients and healthcare services should earn from the use of medications. The paper proposes four possible channels of legislative intervention that could tackle conflicts of interests and economic inefficiencies in the market of drugs and in healthcare services.